An AIE-Active conjugated macrocyclic tetramaleimide for "Turn-On" far red/near-infrared fluorescent bioimaging. (June 2021) - Zeng, Wei; Zhu, Ling-Yun; Chen, Yong; Lin, Mei-Jin
Abstract: A novel water-soluble conjugated macrocyclic tetramaleimide (WCMT-1) with far red/near-infrared (FR/NIR) fluorescence emission has been rationally designed and successfully synthesized. WCMT-1 with the twisted donor (D) and acceptor (A) structures make it possess both aggregation-induce emission (AIE) and twist intramolecular charge transfer (TICT) characteristics. Due to the AIE effects, WCMT-1 exhibits a strong fluorescence in non-polar solvents (the quantum yield of WCMT-1 reaches to 33.7% in toluene and 32.5% in CCl4 ), but it is quenched in an aqueous solution caused by the TICT process. However, by the introduction of sodium lauryl sulfonate (SLS) into the WCMT-1 aqueous solution, the in situ generated WCMT-1&SLS supra-amphiphile resulted in remarkable recovery of FR/NIR fluorescence. Furthermore, combined with its large Stokes shift and good water solubility, the bioimaging experiments towards HeLa and HepG2 cells have also been conducted to give a good performance. Graphical abstract: A water-soluble conjugated macrocyclic tetramaleimide with D-A structural features and AIE-activated FR/NIR emission properties has been developed and the "turn-on" fluorescent bioimaging has been conducted. Image 1 Highlights: A novel water-soluble conjugated macrocyclic tetramaleimide (WCMT-1) with far red/near-infrared (FR/NIR) fluorescence emission has been synthesized. WCMT-1 possesses both aggregation-induce emission (AIE) and twist intramolecular charge transfer (TICT) characteristics. A remarkable recovery of FR/NIR fluorescence for WCMT-1 in aqueous solution could be achieved by the introduction of sodium lauryl sulfonate (SLS). The bioimaging experiments towards HeLa cells and HepG2 cells for WCMT-1&SLS have also been conducted. This study suggests that WCMT-1 is a promising bioprobe for organic-solvent-free bioimaging.